FROM CONTROVERSY TO TOLERANCE: Dynamics of the Development of Istiqomah Mosque in Front of a Church in Ungaran Central Java Indonesia (State Islamic University (UIN) of Sunan Ampel Surabaya, 2017)
This study aims to reveal the dynamic of the development of a mosque in front of a church: the case study of Istiqomah Mosque of Ungaran. The dynamics of the development is seen from some factors that encouraged the establishment of the mosque, the phenomenon of controversy, the problem solution, and the development of tolerance model. The study uses a historical-qualitative approach. The primary data are gathered from interviews, documentation, and observation. The purposes of building the mosque were to balance the national development, to prevent the influence of the Partai Komunis Indonesia (PKI, Indonesian Communist Party), and to create a symbol of tolerance. Controversy occurred in the process of construction because some political and religious elites considered the mosque as political Islam. The controversy waned after the New Order’s elites supported the construction of the mosque. The implementation of a moderate Islamic principles influenced the mosque in building tolerance to the Kristus Raja church in front of it.